Investigación sobre procesos de enseñanza – aprendizaje de las cuestiones energéticas desde el inicio de la educación energética - Castro-Montaña, Jhonn Edgar (Revista Científica, 2016)
An approach to a state of the art of advanced research on teaching and learning processes of energy issues in science teaching during the development of energy education between 1972-2011, a period in which four types of Research results: One that refers to studies referring to the purely conceptual approach to energy issues